T-DLRP: Detection of Fast Retransmission Losses Using TCP Timestamp for Improving the End-to-End Performance of TCP over Wireless Networks. (17th December 2013) - Sreekumari, Prasanthi; Chung, Sang-Hwa; Lee, Meejeong; Kim, Won-Suk
Improving the end-to-end performance of TCP over wireless networks has been an active research area. When TCP operates in wireless networks, the performance of TCP degrades significantly. It is well known that frequent retransmission timeouts are the leading source of TCP performance degradation over wireless networks. Retransmission timeouts are unavoidable, when the fast retransmission of a lost packet fails to reach the destination. There have been many schemes developed for reducing the retransmission timeouts of TCP. However, these schemes have no mechanism to detect the loss of fast retransmitted packets over wireless networks. In this paper, we introduce an efficient TCP mechanism, called T-DLRP, which is able to detect the loss of fast retransmitted packets and react accordingly. To justify our contributions, we compared T-DLRP against TCP New Reno, Vegas, New Jersey, Veno, Cerl, and DAC via extensive simulations using Qualnet 4.5 simulator. The results demonstrate that our mechanism achieves significant improvement over existing TCP variants especially in a coexisted network with packet loss and fast retransmission losses. Compared to DAC, T-DLRP gains more than 70% improvement in terms of accuracy over wireless networks. Also, our experiments of multiple connections of the same TCP flows reveal that T-DLRP has better fairness compared to TCP NewReno.